Crunch time in the NBA - The effectiveness of different play types in the endgame of close matches in professional basketball - Christmann, J.; Akamphuber, M.; Müllenbach, A. L.; Güllich, A. (International Journal of Sports Science & Coaching, 2018)
In professional basketball, the final few possessions often determine the result of a game. The coach`s decision on tactics may be critical to a team`s win or loss. This study investigated offense play types in the endgame (final 120s) of 115 close basketball matches (=5 points score differential) in the National Basketball Association. We video-analysed 996 plays and assessed the frequencies and outcomes of six defined play types: 1×1 without isolation; 1×1 with isolation; pick-and-roll; complex team play; inbound play; and transition play. Analyses revealed that pick-and-roll was employed the most and inbound play the least frequently. The 1×1 with or without isolation were the least effective play types, averaging 0.9-1.0 pts/possession. They were rather `static` and exhibited relatively long duration, low action frequency (passes, screens, handoffs, cuts, drives) and high defence pressure on the shooter. In contrast, transition, inbound and complex team plays were the most effective (means 1.3-1.5 pts/possession). They displayed greater spatial dynamics either through motion speed (transition) or high action frequency (complex and inbound plays), and either led to over-represented uncontested shots or over-represented offensive rebounds and their effective utilisation. Pick-and-roll play was intermediate in these regards. Overall, plays led to 0.8 pts/possession when being in the lead vs. 1.4 pts/possession when being down. Increased spatial dynamics through high motion speed and/or high frequency of concatenated cooperative manoeuvres enhance the success probability of endgame play types in professional basketball.